Announcing the 2016 Pharmaceuticals Travel Award for Young Investigators - Jean Jacques Vanden Eynde (MDPI AG, 2016)
For the ﬁrst time in its short history, our journal is able, this year, to support a young researcher in the ﬁeld of medicinal chemistry by offering a travel grant of 800 CHF.[...]